FUNDAMENTOS E POLÍTICAS EDUCACIONAIS: HISTÓRIA, MEMÓRIA E TRAJETÓRIA DA EDUCAÇÃO NA BAHIA - Doi: http://dx.doi.org/10.5212/PublicatioHum.v.16i2.209224 - Nunes, Antonietta d´Aguiar (Publicatio UEPG: Ciências Sociais Aplicadas, 2009)
O artigo conceitua Fundamentos, Política, Política educacional e elenca características de um sistema organizado de ensino público. Discorre sobre os antecedentes da organização do arcabouço baiano de ensino, desde o início do séc. XIX com a vinda da Família Real portuguesa para o Brasil; fala da situação do ensino na capitania depois província da Bahia durante o reinado do Principe Regente depois rei d. JoãoVI, do governo baiano do 8º conde dosArcos (1809-1818) e suas realizações educacionais, da educação na Bahia no tempo do imperador Pedro I (1822-1830) e da Regêcia Trina Permenente até 1834.Menciona oAtoAdicional à Constituição de 1824 e a criação das Assembléias legislativas provinciais. Depois descreve a organização do sistema provincial baiano de ensino público através das leis e regulamentos emitidos pela Assembléia Legislativa provincial da Bahia, mencionando alguns anos que julga marcantes numa possível periodização da educação baiana. Fala da situação do ensino baiano durante a primeira república, da educação durante a segunda República na Bahia, no Estado Novo (1937-1945), na Redemocratização de 1946 a 1964, no governo policial-militar de 1964 a 1985; menciona a Implantação da LDB 5.692/71 na Bahia e o retorno às eleições diretas para o poder executivo, narrando os administradores, as políticas educacionais e as instituições públicas e privadas de ensino mais importantes criadas na Bahia em cada um destes governos, não esquecendo da introdução dos estudos africanos, História da África e afro-brasileiridades. This article conceptualizes fundaments, politics, educational policies and presents the characteristics of a particular public teaching system. It describes the history of the teaching framework in Bahia since the beginning of 19th century with the coming of the Portuguese royal family to Brazil. The article discusses a number of issues from the teaching situation at the time of the captaincy which later became province of Bahia during the reign of the Regent Prince (later king Don João VI), the government of the 8th count of Arcos in Bahia (1809-1818) and his educational accomplishments; the education in Bahia during the reign of the Emperor Pedro I(1822-1830) and during the period of the Triple Permanent Regency until 1834. Next, the AdditionalAct to the Brazilian constitution of 1824 and the creation of the Provincial Legislative Assemblies are described. The next issues described are the organization of the provincial system of public teaching in Bahia and the important years for the division into periods of education in Bahia. After this, the situation of education during the First Republic (1889-1930), during the Second Republic and New State (1937-45), the redemocratization from 1946 to 1964, during the military political government from 1964 to 1985 are presented. Following this, the implementation of the National Guidelines 5.692/71 in Bahia and the return of direct elections are discussed and special attention is given to the governors, the educational policies and the public and private teaching institutions created in Bahia in each of the governments, including the introduction of African studies, History of Africa and Afro-Brazilian issues. Keywords: Educational policies. Education in Bahia. Organization of public mainstream education in Bahia. Directors of instruction and educational secretaries in Bahia.